2010
DOI: 10.1007/s10646-010-0579-8
|View full text |Cite
|
Sign up to set email alerts
|

B-esterase activities and blood cell morphology in the frog Leptodactylus chaquensis (Amphibia: Leptodactylidae) on rice agroecosystems from Santa Fe Province (Argentina)

Abstract: Activity of B-esterases (BChE: butyrylcholinesterase and CbE: carboxylesterase using two model substrates: α-naphthyl acetate and 4-nitrophenyl valerate) in a native frog, Leptodactylus chaquensis from rice fields (RF1: methamidophos and RF2: cypermethrin and endosulfan sprayed by aircraft) and non-contaminated area (pristine forest) was measured. The ability of pyridine-2-aldoxime methochloride (2-PAM) to reactivate BChE levels was also explored. In addition, changes in blood cell morphology and parasite infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 51 publications
2
30
0
4
Order By: Relevance
“…Bernal-Hernández et al (2010) showed than AChE activity was 65% lower in another bivalve, Crassostrea corteziensis, from Boca de Camichín than in control oysters, in a subtropical Mexican Pacific estuary, suggesting the presence of OP and CAR pesticides in these aquatic environments. In a similar study performed in Argentina, Attademo et al (2011) reported that BChE activity was lower in a native frog, Leptodactylus chaquensis, from rice fields where pesticides such as methamidophos (OP), cypermethrin (pyrethroid) and endosulfan (organochloride) were used, as compared to those from a reference site. In contrast, Printes et al (2011) did not observe an association of cholinesterase (ChE) activity in Chironomus xanthus with exposure to sediments containing pesticides from Monjolinho River (Southeast Brazil); the authors suggested that the selected biomarker was not sensitive and specific enough to detect the effects of pesticide contamination at the levels measured in the study area.…”
Section: Biomarkers Of Pesticide Exposure In Aquatic Organisms and Humentioning
confidence: 99%
See 1 more Smart Citation
“…Bernal-Hernández et al (2010) showed than AChE activity was 65% lower in another bivalve, Crassostrea corteziensis, from Boca de Camichín than in control oysters, in a subtropical Mexican Pacific estuary, suggesting the presence of OP and CAR pesticides in these aquatic environments. In a similar study performed in Argentina, Attademo et al (2011) reported that BChE activity was lower in a native frog, Leptodactylus chaquensis, from rice fields where pesticides such as methamidophos (OP), cypermethrin (pyrethroid) and endosulfan (organochloride) were used, as compared to those from a reference site. In contrast, Printes et al (2011) did not observe an association of cholinesterase (ChE) activity in Chironomus xanthus with exposure to sediments containing pesticides from Monjolinho River (Southeast Brazil); the authors suggested that the selected biomarker was not sensitive and specific enough to detect the effects of pesticide contamination at the levels measured in the study area.…”
Section: Biomarkers Of Pesticide Exposure In Aquatic Organisms and Humentioning
confidence: 99%
“…AChE inhibition has been used as one standard method to detect OP exposure (Holmstedt, 1959), but this assessment has disadvantages, as intra-and inter-subject variabilities are about 10% in the same person and about 10-40% among subjects (Lotti, 1995), respectively. The integrated use of several biomarkers, such as cholinesterases and others, may be necessary for biomonitoring programs to diagnose pesticide exposure in wild populations (Attademo et al, 2011). Thus, it was proposed that other biomarkers should be identified and characterized, such as the esterase identified as acetyl peptide hydrolase (APH), which was inhibited by some OP (Quistad et al, 2005).…”
Section: Esterase Inhibition As a Biomarker Of Pesticide Exposure In mentioning
confidence: 99%
“…The two observation periods were selected based on previous works (Sánchez et al, 1997;Lajmanovich et al, 2009;Attademo et al, 2011). All the animals captured were males because they are easily identified in the field by their calls and to minimize population impact (ASIH et al, 2001); gravid females were avoided.…”
Section: Animal Samplingmentioning
confidence: 99%
“…However, most of the studies with vertebrate esterases have been addressed on the following issues: (1) enzymatic characterization of blood ChE activity for enzyme assay purposes (e.g., Küster 2005;Attademo et al 2007;Lajmanovich et al 2010), (2) chemical reactivation of the phosphorylated ChE activity using oximes (e.g., Lajmanovich et al 2008), (3) relationship between ChE inhibition and physiological or behavioral changes (e.g., Fildes et al 2009;Junges et al 2010), and (4) field monitoring of OP/CM pesticide exposure by comparing blood ChE activity between pesticide-exposed and nonexposed populations (e.g., Attademo et al 2011). But most of the studies examining the sources of natural variation of blood esterases in wild vertebrates are particularly limited to birds.…”
Section: Impact Of Confounding Variables On Esterase Activitymentioning
confidence: 99%